Identification of silver cubic structures during ultrasonication of chitosan AgNO3 solution. (5th November 2016) - Raghavendra, Gownolla Malegowd; Jung, Jeyoung; Kim, Dowan; Varaprasad, Kokkarachedu; Seo, Jongchul
Highlights: Silver cubic structures were identified during ultrasonication of chitosan AgNO3 solution. Temperature influences the formation of cubic structures. 'Four petal flower-like' structure transforms to 'cubic structure'. Aging of the reaction mixture led to complete dendrites. Abstract: During ultrasonication of chitosan AgNO3 solution (10 mM), silver cubic structures were identified along with other dispersed silver nanoparticles. Temperature influenced the formation of the cubic structures. Formation of the silver cubic structures occurred via initial formation of 'four petal flower-like' structures that underwent transformation to the "cubic morphology" in the latter stages. Aging of the reaction mixture led to formation of complete dendrites. These dendrites comprised a large quantity of silver nanoparticles. Upon repetition of the experiment with starch instead of chitosan, the identified silver cubic structures were completely absent, indicating that formation of the 'silver cubic structures' is dependent on the polysaccharide used. It is believed that the structural features of chitosan facilitate the formation of 'silver cubic structures' under ultrasonic conditions. The phenomena occurring during the experiments were evaluated via scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), ultraviolet-visible (UV–vis) spectra, transmission electron microscopy (TEM), and selected area electron diffraction (SAED) analysis.